On the overall accuracy of the Modified Wöhler Curve Method in estimating high-cycle multiaxial fatigue strength - Luca Susmel (Fracture and Structural Integrity)
The aim of the present paper is to systematically investigate the accuracy of the so-called Modified Wöhler Curve Method (MWCM) in estimating high-cycle fatigue strength of plain and notched engineering materials damaged by in-service multiaxial load histories. In more detail, the MWCM, which is a bi-parametrical critical plane approach, postulates that initiation and Stage I propagation of fatigue cracks occur on those material planes experiencing the maximum shear stress amplitude (this being assumed to be always trueindependently from the degree of multiaxiality of the applied loading path). Further, the fatigue damage extent is hypothesised to depend also on the maximum stress perpendicular to the critical plane, the mean normal stress being corrected through the so-called mean stress sensitivity index (i.e., a material constant capable of quantifying the sensitivity of the assessed material to the presence of superimposed static stresses). In the present investigation, the overall accuracy of the MWCM in estimating high-cycle fatigue strength was checked through 704 endurance limits taken from the literature and generated, under multiaxial fatigue loading, by testing both plain and notched samples made of 71 different materials. Such a massive validation exercise allowed us to prove that the MWCM is highly accurate, resulting in 95% of the estimates falling within an errorinterval equal to ±15%.